Determinants of zakah compliance Intention behaviour on savings among lecturers in Kedah Matriculation College - Nurul Farida, Abdullah (2014)
The collection of zakah on saving is the third highest collection reported by Jabatan Zakat Negeri Kedah. The previous literature reported that many factors that can influence the compliance behaviour of zakah especially zakah on employment income. Therefore, this study was conducted to identify the variables that influence the intention to comply zakah on savings. This study applied the theory of planned behaviour by adding knowledge in an attempt to predict compliance intention behaviour towards zakah on savings. The objective of the study was to determine the relationship between the variables of attitude, subjective norm, perceived behavioural control and knowledge with zakah compliance intention on savings. Thus, this study aims to identify the most important factors between attitude, subjective norm, perceived behavioural control and knowledge that influencing the zakah compliance intention by using multiple regression methods. Data were generated from 106 Muslim lecturers in Kedah Matriculation College. The results revealed that subjective norms and perceived behavioural control were found positive and significantly related to intention to comply zakah on savings whilst the attitudes and knowledge suggests otherwise. Perceived behavioural control was found to be the most important factor influences intention to pay zakah on savings among lecturers in Kedah Matriculation College. Some recommendations are also discussed to improve the compliance behaviour towards zakah on savings